Experimental study on strain of SFRC tunnel lining segments using a comprehensive embedded optical fiber sensing system - Wang, Shun (2024)
In comparison to current techniques, optical fiber sensors (OFS) for structural health monitoring (SHM) of steel fibre reinforced concrete (SFRC) tunnel lining segments is an emerging technology that could enhance tunnel safety and reliability. However, the utilizing many measurement techniques in a single OFS technology has pros and cons, making it difficult to meet the demands for a comprehensive and reliable assessment for long-term monitoring inside tunnels. We present comprehensive OFS system for strain monitoring inside concrete tunnel lining segments. The system involves distributed optical fiber sensing (DOFS) cable, fiber Bragg grating (FBG) sensors, and chirped fiber Bragg grating (CFBG) sensors. The proposed system is particularly useful for high-risk or difficult-to-access locations, such as inside tunnel structures. We provide the deployment design after introducing the sensing principle of the system. To validate its effectiveness and reliability, we conduct a scaled-down laboratory experiment to evaluate the strain behavior. The proposed comprehensive OFS system accurately captures the strain evolution over time in various stages of tunnel lining segments, including casting, curing, loading, and even after failure. This system demonstrates high-resolution, and reliable monitoring of internal strain in tunnel lining segments, making it suitable for practical application in full-scale and long-term SHM during the construction and operation stages of shield tunnels with connection expansion for segments.